Strengthening Skills and Employability in Peru : Final Report - World Bank (Washington, DC, 2013)
This report presents the final results and conclusions of a multi-year program developed by a team comprising Bank staff and first-rate Peruvian researchers, which provides policy-relevant analysis of the constraints to labor market entry for low income workers. Expanding employment opportunities and addressing the deficits in skills of large segments of the labor force have become a central concern for policy makers, the business community, academics, and the society at large in Peru. The study of the labor market and skills acquisition is not an empty field in Peru. Many local analysts have undertaken several studies of the education and training systems and the associated labor market returns. However, up to now data limitations have precluded detailed analyses of the constraints of low-income workers, particularly youth, to map their skills into suitable jobs, and to acquire the skills demanded by the labor market. This is, in fact, generally the case throughout Latin America and in many countries in the developing world. It is hoped that this effort and the report can contribute to inform the discussions of the future of social and employment policy among policy makers and the Peruvian society at large.